A Brief Mindfulness-Based Family Psychoeducation Intervention for Chinese Young Adults With First Episode Psychosis: A Study Protocol - Lo, Herman Hay-Ming; Ho, Wing-Chung; Lau, Elsa Ngar-Sze; Lo, Chun-Wai; Mak, Winnie W. S.; Ng, Siu-Man; Wong, Samuel Yeung-Shan; Wong, Jessica Oi-Yin; Lui, Simon S. Y.; Lo, Cola Siu-Lin; Lin, Edmund Chiu-Lun; Poon, Man-Fai; et al. (Frontiers in Psychology, 2019)
Family psychoeducation has been recommended as a major component in the treatment of psychosis. Many previous studies have implemented an intensive program design that often only emphasized improvements in patients’ illness outcomes but the benefits for caregivers were limited. There have been calls for a time-limited but cost-effective family psychoeducation program to mitigate the looming reality of the suffering of people with psychosis and their families. A Brief Mindfulness-Based Family Psychoeducation for psychosis program is developed to reduce caregivers’ burden and promote young adult’s recovery. A randomized controlled trial will be conducted to compare this intervention with an ordinary family psychoeducation intervention. Both arms will involve six sessions, with a total contact time of 12 hours. 300 caregivers of young adults who have experienced first episode psychosis within last three years will be recruited. Program effectiveness will be assessed by comparing outcomes measuring the caregivers’ burden, mental health symptoms, positive well-being, and the young adult’s mental health symptoms during the study and at nine-month post-randomization. The role of expressed emotions, interpersonal mindfulness, and non-attachment in mediating these outcomes will be explored. An additional qualitative approach Photovoice is selected to explore the complex family experiences and the benefits of mindfulness from the caregivers’ personal perspectives. Trial Registration: The trial is registered with the United States Clinical Trials Registry (ClinicalTrials.gov): NCT03688009.